Epidemiological status of depressive disorders in the Middle East and North Africa from 1990 to 2019 - Mehdi Moradinazar; Parmida Mirzaei; Saied Moradivafa; Mahdieh Saeedi; Mona Basiri; Mohammad Shakiba (Tabriz University of Medical Sciences, 2022)
Background: Depressive disorders are one of the most common mental health diseases, which are associated with adverse life events such as increased risk of self-injury. This study was aimed to measure the epidemiological status and the burden of depressive disorders in the Middle East and North Africa (MENA) countries. Methods: The study population included 21 countries in the MENA region, covering a population of about 600 million. The Global Burden of Disease (GBD) 2019 database was used. The disability-adjusted life years (DALYs) were estimated by the years lived with disability (YLDs) component. The prevalence, incidence, and the DALYs rates per 100000 people by age-standardized rate (ASR) were measured. Results: In 2019, the highest prevalence 6198.95 (95% uncertainty interval [UI], 5402.41- 7108.39), incidence 7864.2 (95% UI, 6719.71-9216.83), and DALYs 1168.68 (95% UI, 802.95- 1624.31) per 100,000 were in Palestine by ASR. Between 1990 and 2019, the depressive disorders-related prevalence, incidence, and DALYs rates in the MENA region increased by 0.004%, 0.006%, and 0.005%. The highest increment of the prevalence, incidence, and DALYs rates was related to Saudi Arabia by 0.05%, 0.064%, and 0.055%. The highest percentage of major depressive disorder (MDD)-related DALYs attributed to intimate partner violence was related to Iran (101.1). Also, the highest percentage of MDD-related DALYs attributed to childhood sexual abuse (34.26) and bullying victimization (49.81) was related to Palestine. Conclusion: Given the increasing trend of depressive disorders in MENA region, mental health programs should be prioritized across the MENA countries, with significant contributions and involvement of the governments.